The influence of HIV and schistosomiasis on renal function: a cross-sectional study among children at a hospital in Tanzania. - Neema M Kayange; Luke R Smart; Jennifer A Downs; Mwanaisha Maskini; Daniel W Fitzgerald; Robert N Peck (Public Library of Science (PLoS), 2015)
Schistosomiasis and HIV are both associated with kidney disease. Prevalence and factors associated with abnormal renal function among HIV-infected children in Africa compared to uninfected controls have not been well described in a schistosomiasis endemic area.This cross-sectional study was conducted at the Sekou Toure Regional Hospital HIV clinic in Mwanza, Tanzania. A total of 122 HIV-infected children and 122 HIV-uninfected siblings were consecutively enrolled. Fresh urine was obtained for measurement of albuminuria and Schistosoma circulating cathodic antigen. Blood was collected for measurement of serum creatinine. Estimated glomerular filtration rate (eGFR) was calculated using the modified Schwartz equation. Renal dysfunction was defined operationally as eGFR<60 mL/min/1.73 m2 and/or albuminuria>20 mg/L in a single sample. Among 122 HIV-infected children, 61/122 (50.0%) met our criteria for renal dysfunction: 54/122 (44.3%) had albuminuria>20 mg/L and 9/122 (7.4%) had eGFR<60. Among 122 HIV-uninfected children, 51/122 (41.8%) met our criteria for renal dysfunction: 48/122 (39.3%) had albuminuria>20 mg/L and 6/122 (4.9%) had eGFR<60. Schistosomiasis was the only factor significantly associated with renal dysfunction by multivariable logistic regression (OR = 2.51, 95% CI 1.46-4.31, p = 0.001).A high prevalence of renal dysfunction exists among both HIV-infected Tanzanian children and their HIV-uninfected siblings. Schistosomiasis was strongly associated with renal dysfunction.